Investigation on the Coupling Effect of Bionic Micro-Texture Shape and Distribution on the Tribological Performance of Water-Lubricated Sliding Bearings - Xiansheng Tang; Yunfei Lan; Sergei Bosiakov; Michael Zhuravkov; Tao He; Yang Xia; Yongtao Lyu (Lubricants)
Water-lubricated bearings (WLB), due to their pollution-free nature and low noise, are increasingly becoming critical components in aerospace, marine applications, high-speed railway transportation, precision machine tools, etc. However, in practice, water-lubricated bearings suffer severe friction and wear due to low-viscosity water, harsh conditions, and contaminants like sediment, which can compromise the lubricating film and shorten their lifespan. The implementation of micro-textures has been demonstrated to improve the tribological performance of water-lubricated bearings to a certain extent, leading to their widespread adoption for enhancing the frictional dynamics of sliding bearings. The shape, dimensions (including length, width, and depth), and distribution of these micro-textures have a significant influence on the frictional performance. Therefore, this study aims to explore the coupling effect of different micro-texture shapes and distributions on the frictional performance of water-lubricated sliding, using the computational fluid dynamics (CFD) analysis. The results indicate that strategically arranging textures across multiple regions can enhance the performance of the bearing. Specifically, placing linear groove textures in the outlet of the divergent zone and triangular textures in the divergent zone body maximize improvements in the load-carrying capacity and frictional performance. This specific configuration increases the load-carrying capacity by 7.3% and reduces the friction coefficient by 8.6%. Overall, this study provided critical theoretical and technical insights for the optimization of WLB, contributing to the advancement of clean energy technologies and the extension of critical bearing service life.